EDUKASI SWAMEDIKASI PENANGANAN DIARE PADA ANAK DI KELOMPOK PKK, PAKUSARI, JEMBER - Dyan Wigati; Dina Trianggaluh Fauziah; Dwi koko pratoko; Wanda Tri Agustin; Rahmadania Affelia Dianto; Carolyn Octavia Cornelyanto; Ayu Safitri (LPPM Universitas dr. Soebandi, 2026)
Diarrhea is an abnormal condition characterized by excessive stool, watery consistency, which may blood and mucus. Self-medication is the self-administration of drugs or herbal remedies to treat minor illnesses or symptoms. The aim of this activity is enhance maternal knowledge and practices regarding self-medication for childhood diarrhea through an educational program comprising counseling, interactive discussions, and health screenings. The methodology encompassed a situational analysis and planning, implementation through interactive discussions, and evaluation. The evaluation measured changes in knowledge using a pre-test/post-test design. The findings is a comparative analysis of the pre- and post-test results revealed a marked improvement in the mothers' knowledge of preventive measures and appropriate self-medication actions for managing diarrhea in children. it can be concluded that this program successfully improved the knowledge of the participating mothers. It concluded that this program successfully improved the knowledge of the participating